Sewing Training As A Means Of Developing The Batik Industry And Improving The Welfare Of The Kungkai Community - Nurmaliati; Ilwandri; Indra Wijaya (LPPM Akademi Teknik Adikarya, 2025)
This Community Service was carried out in Kungkai Village, in the form of a batik clothing sewing training to improve the skills and economy of the community. This service is a continuation of the previous training on batik cloth processing, where participants have been taught about batik techniques and batik designs. In this training, 15 participants were divided into 5 groups, with a focus on making women's batik clothing and men's batik clothing. The training method was carried out through direct practice, where each group was taught to sew batik clothing according to the instructor's instructions. The results of this service are expected to improve the community's skills in sewing batik clothing, thereby increasing the income and economy of the Kungkai Village community, as well as increasing the selling value of local batik products.